Prevalence and Related Factors of Insomnia Among Chinese Medical Staff in the Middle and Late Stage of COVID-19 - Liu, Dianying; Liu, Shaohua; Zhu, Lin; Li, Dongbin; Huang, Donghua; Deng, Hongdong; Guo, Huiyun; Huang, Dan; Liao, Yuanping; Mao, Zhongzhen; Miao, Qiumei; Liu, Wanglin; et al. (Frontiers in Psychiatry, 2020)
Background: The outbreak of novel coronavirus disease (COVID-19) has brought serious psychological pressure to people, especially medical health staff. At present, there are few studies on insomnia and related factors of medical health staff in the middle and late stage of the epidemic of COVID-19. Therefore, the purpose of this study was to investigate the prevalence of insomnia and its related risk factors among medical workers in China in the middle and later stage of COVID-19 epidemic, as well as the relationship between insomnia and psychological resilience. Methods: From February 14 to March 29, 2020, a cross-sectional survey was conducted among 606 medical staff in China through Ranxing Technology's "SurveyStar" network platform. All subjects were assessed with the Insomnia Severity Index ((ISI) and simplified Chinese version of Connor-Davidson Resilience scale (CD-RISC-10). Results: In the middle and later stages of the COVID-19 outbreak, the incidence of insomnia among medical staff was 32.0%. Compared with non-insomnia group, the insomnia group had younger age, lower education level, longer daily working hours and less psychological resilience. In addition, the prevalence of insomnia was higher in medical staff with a history of somatic diseases. The severity of insomnia of Chinese medical staff was associated with age, education level, daily working hours, psychological resilience and somatic diseases. Conclusions: Our study shows that nearly 1/3 of Chinese medical workers suffer from insomnia nearly a month after the COVID-19 outbreak. Risk factors for insomnia include younger age, lower education level, longer working hours per day, and physical illness. The tenacious dimension of psychological resilience is a protective factor for insomnia.